Environmental Components and Mechanism of Public-Private Partnership in the Area of Risk Insurance in Crop - BAIMAGAMBETOVA, Zamzagul; ISMAILOVA, Rymkul; KULMAGANBETOVA, Aisulu; KASSIMBEKOVA, Meiramkul; OMARKHANOVA, Zhibek (Journal of Environmental Management and Tourism, 2020)
Crop risk insurance in Kazakhstan is an urgent problem for agricultural producers and insurers, since agriculture is in the zone of constant natural and economic risks, where the main share of risks is associated with weather events affecting the production of agricultural crops. In order to reduce natural risks in agriculture, to ensure the protection of the property interests of farmers in crop production from the consequences of adverse natural phenomena, measures are being taken by the state and business, however, there are problems that both agricultural producers and insurers face. Public-private partnership has established itself as a successful tool for interaction between business and the state, and now in Kazakhstan a lot of work is being done for the qualitative growth and development of the PPP mechanism, which requires more active interaction between the state and business in the field of crop production.